Membangun Customer Satisfaction Melalui Service Quality Dan Customer Trust Di Ruang Rawat Inap Amarilis 2 RSUD Tugurejo Semarang - Lilik Setiawan; Nita Sukmawati (Manajemen Kreatif Jurnal, 2025)
This study aims to measure the model of achieving customer satisfaction through service quality and influenced by customer trust. Data collected from 100 inpatients of Amarilis 2 room of RSUD Tugurejo Semarang. processed using Structural Equation Model-Partial Least Square (SEM-PLS) modeling technique. The results showed that service quality positively and significantly affects customer trust of inpatients of Amarilis 2 room of RSUD Tugurejo Semarang. Customer trust and service quality variables have a significant positive effect on customer satisfaction of inpatients of Amarilis 2 room at Tugurejo Semarang Hospital. This research contributes to the management of Amarilis 2 room of Tugurejo Hospital Semarang by providing appropriate strategies to understand customer satisfaction of inpatients of Amarilis 2 room of Tugurejo Hospital Semarang. This strategy is then expected to boost the increase of customer satisfaction of inpatients of Amarilis 2 room of RSUD Tugurejo Semarang. The novelty of this study lies in the fact that it is the first to empirically use the service quality model through excellent service by integrating customer trust to analyze customer satisfaction of inpatients of Amarilis 2 room of RSUD Tugurejo Semarang.